Analisis Strategi Management Waktu dalam Meningkatkan Produktivitas Belajar Untuk Menghindari Stress Akademik Pada Mahasiswa - Salwa Tadzkirotul Aula; Rachil Najma Shifa; Dewi Khurun Aini (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Education in higher education requires students to face a variety of challenging academic and social tasks and responsibilities, both on campus and around where they live. Adapting and organizing yourself well is the key to facing this challenge. Students have the freedom to set their own academic goals and objectives. The aim of this research is to analyze time management strategies in increasing learning productivity to avoid academic stress in students. The main study in this research focuses on the strategies used by students to increase productivity in learning and avoid academic stress. Data collection in this research was through in-depth interviews and documentation. This research applies a qualitative approach, where this method is used to obtain an in-depth understanding and explain phenomena by investigating non-numerical data through collection, analysis and interpretation. The results of this research highlight appropriate time management strategies in increasing learning productivity, by managing time wisely. well, individuals can prioritize tasks that have a big impact and are likely to be postponed, thereby ensuring timely completion. By implementing time management, we can use time efficiently and increase productivity in studying.